Religion and Politics: Reflections from Jakarta - Nursheila Muez (2017)
Ahok’s defeat in the Jakarta gubernatorial election and his conviction for blasphemy have reignited debates about the role of Islam in a secular state. Misconceptions about the relationship between the two need to be addressed.